Russia in Europe - Bell, Andrew, 1726-1809 (engraver):::Creator::::::::::::; Macfarquhar, Colin, b. 1745-1795 (author):::Contributor:::::::::::: (United Kingdom)
Map of Russia's European territories from the early nineteenth century.